EPIGENETIC MECHANISMS OF BREASTFEEDING IN IMMUNE SYSTEM DEVELOPMENT - Qahramonov Davron Dilshod o‘g‘li (World Scientific Research Journal, 2025)
The immune system undergoes a crucial developmental stage in the early stages of life. In this process, breast milk plays a particularly significant role not only with its nutritional and protective functions but also with its epigenetic effects. Our research analyzes how bioactive components in breast milk (microRNAs, molecules affecting DNA methylation, factors controlling histone modification) perform epigenetic regulation through the differentiation and expression of immune cells. This article focuses on analyzing the impact of breast milk on immunogenesis from an epigenetic perspective, proposing new scientific approaches that prove the importance of early feeding in the development of the immune system.